A Novel Paradigm Based on ST2 and Its Contribution towards a Multimarker Approach in the Diagnosis and Prognosis of Heart Failure: A Prospective Study during the Pandemic Storm - Radu-Stefan Miftode; Daniela Constantinescu; Corina Maria Cianga; Antoniu Octavian Petris; Amalia-Stefana Timpau; Adrian Crisan; Irina-Iuliana Costache; Ovidiu Mitu; Dana-Teodora Anton-Paduraru; Ionela-Larisa Miftode; Mariana Pavel-Tanasa; Petru Cianga; et al. (Life, 2021)
Background: Acute heart failure (HF) represents an increasingly common and challenging presentation in the emergency room, also inducing a great socio-economic burden. Extensive research was conducted toward finding an ideal biomarker of acute HF, both in terms of sensitivity and specificity, but today practicians’ interest has shifted towards a more realistic multimarker approach. Natriuretic peptides (NPs) currently represent the gold standard for diagnosing HF in routine clinical practice, but novel molecules, such as sST2, emerge as potentially useful biomarkers, providing additional diagnostic and prognostic value. Methods: We conducted a prospective, single-center study that included 120 patients with acute HF and 53 controls with chronic HF. Of these, 13 patients (eight with acute HF, five from the control group) associated the coronavirus-19 disease (COVID-19). The diagnosis of HF was confirmed by a complete clinical, biological and echocardiographic approach. Results: The serum levels of all studied biomarkers (sST2, NT-proBNP, cardiac troponin) were significantly higher in the group with acute HF. By area under the curve (AUC) analysis, we noticed that NT-proBNP (AUC: 0.976) still had the best diagnostic performance, closely followed by sST2 (AUC: 0.889). However, sST2 was a significantly better predictor of fatal events, showing positive correlations for both in-hospital and at 1-month mortality rates. Moreover, sST2 was also associated with other markers of poor prognosis, such as the use of inotropes or high lactate levels, but not with left ventricle ejection fraction, age, body mass index or mean arterial pressure. sST2 levels were higher in patients with a positive history of COVID-19 as compared with non-COVID-19 patients, but the differences were statistically significant only within the control group. Bivariate regression showed a positive and linear relationship between NT-proBNP and sST2 (r(120) = 0.20, p < 0.002). Conclusions: we consider that sST2 has certain qualities worth integrating in a future multimarker test kit alongside traditional biomarkers, as it provides similar diagnostic value as NT-proBNP, but is emerging as a more valuable prognostic factor, with a better predictive value of fatal events in patients with acute HF.